Evaluating the impact of climate change on fluvial flood risk in a mixed-use watershed. (December 2019) - Xu, Xin; Wang, Yu-Chen; Kalcic, Margaret; Muenich, Rebecca Logsdon; Yang, Y.C. Ethan; Scavia, Donald
Abstract: Predicting flood risk is important for climate change adaptation. We quantify fluvial flood risk due to changing climate in a mixed-use watershed in Michigan, USA. We apply two approaches to project future climate change: an ensemble of temperature and precipitation perturbations on the historical record and an ensemble of global and regional climate models. We incorporate climate projections into the Soil and Water Assessment Tool (SWAT) to estimate daily streamflow, then quantify flood risk using indices related to flood probability, duration, magnitude, and frequency. Results indicate rising temperatures may counteract small increases in precipitation, likely due to increased evapotranspiration. Climate model data without bias correction used in SWAT produced reasonable future streamflow changes—similar to the perturbation of historical climate—therefore retaining the predicted change in the flood frequency distribution. This work advances the application of climate models in SWAT for flood risk evaluation at watershed scales. Highlights: Four flood indices were used to assess different aspects of flooding due to climate change. Driving a watershed model with climate model output that was not bias-corrected gave reliable hydrologic prediction. Rising temperatures counter-acted greater precipitation and led to reduced flood risk in the mid-century. A threshold of 10% increase in precipitation produced greater flood risk, and below rising temperatures had a greater impact. The spatial variability in flood risk varied based on land use, soils, and slopes.